2022
DOI: 10.3390/brainsci13010015
|View full text |Cite
|
Sign up to set email alerts
|

Research Hotspots and Frontiers of Transcranial Direct Current Stimulation in Stroke: A Bibliometric Analysis

Abstract: Background: Over the past decade, many studies in the field of transcranial direct current stimulation (tDCS) in stroke have been published in scholarly journals. However, a scientometric analysis focusing on tDCS after stroke is still missing. The purpose of this study is to deliver a bibliometric analysis to investigate the global hotspots and frontiers in the domain of tDCS in stroke from 2012 to 2021. Methods: Articles and reviews related to tDCS in stroke were retrieved and obtained from the Web of Scienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…18,19 Transcranial direct current stimulation (tDCS) is a non-invasive neuroregulatory technique that uses constant low-intensity direct current (1-2 mA) to modulate neuronal activity in the cerebral cortex. 20,21 The excitability of the affected side decreased and the compensatory excitability of the unaffected side increased after unilateral stroke. 22 Studies have shown that the anode tDCS can depolarize the neuronal potential of the brain to enhance cortical excitability, while the cathode can hyperpolarize the neuronal potential to reduce cortical excitability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 Transcranial direct current stimulation (tDCS) is a non-invasive neuroregulatory technique that uses constant low-intensity direct current (1-2 mA) to modulate neuronal activity in the cerebral cortex. 20,21 The excitability of the affected side decreased and the compensatory excitability of the unaffected side increased after unilateral stroke. 22 Studies have shown that the anode tDCS can depolarize the neuronal potential of the brain to enhance cortical excitability, while the cathode can hyperpolarize the neuronal potential to reduce cortical excitability.…”
Section: Introductionmentioning
confidence: 99%
“…Transcranial direct current stimulation (tDCS) is a non‐invasive neuroregulatory technique that uses constant low‐intensity direct current (1–2 mA) to modulate neuronal activity in the cerebral cortex 20,21 . The excitability of the affected side decreased and the compensatory excitability of the unaffected side increased after unilateral stroke 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Bibliometrics, first proposed by Pritchard in 1969, refers to the quantitative analysis of the target literature in order to uncover potential key information, generalize patterns of knowledge, and outline trends in the vast amount of literature data. [ 18 ] Bibliometric analysis has provided clear insights into many areas of medicine, [ 19 ] such as stroke treatment [ 20 , 21 ] and cancer rehabilitation. [ 22 , 23 ] By reading such studies, researchers are able to identify important journals, scholars, national institutions, and collaborations, [ 24 ] and keep abreast of research hotspots and trends in some fields.…”
Section: Introductionmentioning
confidence: 99%